Karakteristik Membran Komposit Polietersulfon, Polivinilpirolidon dan Kitosan - Muhammad Fadli; Al Khausar; Sofyana Sofyana; Ummi Fathanah (Fakultas Teknik, 2021)
Polyethersulfone (PES) is a membrane forming material that has many advantages but is hydrophobic, so it is necessary to add other materials, such as composite PES with Polyvinylpyrrolidone (PVP) and chitosan. The addition of PVP aims to change the nature of the PES membrane to be hydrophilic and the addition of chitosan aims to improve the mechanical properties of the polymer. The purpose of this study was to study the effect of adding PVP and chitosan to the characteristics of PES membranes. The membranes were made using a phase inversion technique by immersion precipitation with a concentration of 20% PES, 1% PVP, and chitosan were varied, namely 0% (M0 membrane), 1.5% (M1), 2% (M2), and 3% (M3). The results of the permeability test showed that the membranes M0, M1, M2, and M3 are classified as nanofiltration membranes with Lp values of 9.1237, 7.618, 6.9651, and 4.4077 L/m2.h.bar. The swelling degree value is 61,512; 103.111; 145,564; and 158.610% and the overall porosity value is 22.892; 32.360; 80.726; and 117.016%. The SEM test showed that the morphology of the membrane changed its structure as the concentration of chitosan increased. The FTIR test on the membrane showed that there were absorption bands, each of which identified its functional group.